2013
DOI: 10.1128/jvi.02363-12
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Requirements for Bluetongue Virus Primary Replication In Vivo

Abstract: The replication mechanism of bluetongue virus (BTV) has been studied by an in vivo reverse genetics (RG) system identifying the importance of certain BTV proteins for primary replication of the virus. However, a unique in vitro cell-free virus assembly system was subsequently developed, showing that it did not require the same set of viral components, which is indicative of differences in these two systems. Here, we studied the in vivo primary replicase complex more in-depth to determine the minimum components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 49 publications
3
83
0
Order By: Relevance
“…5). The NA titers ranged between 16 and 128 for all serotypes tested, and there was no apparent interference with respect to the ability of the animal to respond to each of the vaccine strains present in the cocktail (Fig. 5).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…5). The NA titers ranged between 16 and 128 for all serotypes tested, and there was no apparent interference with respect to the ability of the animal to respond to each of the vaccine strains present in the cocktail (Fig. 5).…”
Section: Resultsmentioning
confidence: 94%
“…Reassortant viruses were rescued from confluent monolayers of complementing cells (BSR9) transfected with six plasmids that drive the expression of BTV proteins VP1, VP3, VP4, VP6, NS1, and NS2 as described previously (16) prior to transfection with seven T7-derived single-stranded RNAs (ssRNAs) from BTV-1, one of the modified S9 (S9⌬ or S9⌬-EGFP) ssRNAs, and a combination of S2 and S6 ssRNAs from a particular serotype.…”
Section: Cells and Viruses Bsr Cells (Bhk-21 Subclone)mentioning
confidence: 99%
“…Thus, live-cell imaging of cells infected with fluorescently labeled poliovirus has revealed that after internalization through a clathrin-, caveolin-, and flotillin-independent, but actin-and tyrosine kinase-dependent, pathway, the virus releases its RNA rapidly from vesicles located very close to the plasma membrane and does not require endocytic acidification or microtubule-dependent transport (14). In this study, however, for the first time, we have successfully identified exposed loop regions in the BTV outer capsid protein VP2 and have generated replication-competent tagged viruses via reverse genetics (28,33). Since, to date, investigation of the functional role of VP2 in BTV entry has been limited to studies based mainly on recombinant protein expression (9), the tagging of VP2 and its successful incorporation into BTV particles have provided valuable insights into its role during virus entry and trafficking.…”
Section: Discussionmentioning
confidence: 84%
“…3B). As described previously (33), uncapped S2 T7 transcripts (BTV1-S2) were generated for all constructs (BTV1-S2 94 , BTV1-S2 352 , and BTV1-S2 420 ) to recover TC-tagged mutant viruses. The reverse genetics system used transfection of BSR cells with 9 T7-derived RNA transcripts (S1 and S3 to S10) together with either wild-type (WT) BTV1-S2 or each of the tagged S2 transcripts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation